Identifying the Role of Book Tax Gap, Executive Character, and Foreign Ownership on Tax Avoidance in Manufacturing Companies Listed in Indonesia Stock Exchange in 2017-2021 - Monica, Rany; Sari, Diana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
: This study aims to determine the effect of the book tax gap, executive character and foreign ownership on tax avoidance. The method of determining the sample using purposive sampling method with a population of 39 companies and 5 (five) years of observation. The type of research used is verification using explanatory survey methods. Data were tested using Eviews 8, statistical methods for testing data quality using descriptive statistics, classic assumption test with normality test, heteroscedasticity test, multicollinearity test and autocorrelation test then panel data regression test and hypothesis testing using t test, f test and coefficient of determination test. The results showed that the book tax gap variable and foreign ownership variable had a significant effect on tax avoidance. Meanwhile, the executive character variable has no significant effect on tax avoidance. Partial test results state that the variable book tax gap, executive character and foreign ownership simultaneously affect tax avoidance.